Helpers in my community - Kalman, Bobbie (New York : Crabtree Pub. Company, 2010)
This book introduces children to the important people who make our communities cleaner, safer, and better. Action shots feature people working in construction, at schools, in hospitals, fighting fires, doing police work, and volunteering.
What is a community? -- Buildings and roads -- Electricity and water -- Teachers and librarians -- Other school helpers -- Medical helpers -- Emergency helpers -- Firefighters -- Police officers -- Kind helpers.
Includes index.
University of Alberta copy in the Canadian Children's Book Centre Depository Collection.
Keywords: Community life -- Juvenile literature